Compromiso laboral del personal de la lavandería La Espuma, de la ciudad de Babahoyo - Mejía Martínez, Carla Alejandra (2019)
The research carried out was aimed at determining the causes of the lack of commitment on the part of the people who work in the laundry "La Espuma". Based on the information obtained, specific factors related to the low predisposition and commitment of employees to the company were evidenced. The research methods used were analytical and inductive, the instrument used was the interview aimed at the entity's staff. The results evidenced the poor work performance, the absenteeism of certain workers, the lack of communication and inappropriate employee-employer relationship, poor work motivation, poor training aimed at optimizing the skills of workers, elements that significantly affect the image, performance and entity productivity